Therapy and Outcomes of Patients with Relapsed Nonmetastatic Rhabdomyosarcoma: A Report from the French Society of Pediatric Oncology Malignant Mesenchymal Tumor Committee - François Sevrin; Emilie Bogart; Daniel Orbach; Marie Cécile Le Deley; Pablo Berlanga; Valérie Bernier; Nadège Corradini; Cindy Fayard; Florent Guerin; Sarah Jannier; Marie Karanian; Stéphanie Proust; et al. (Cancer Medicine)
ABSTRACT Background The prognosis for patients with relapse of localized rhabdomyosarcoma (RMS) remains poor, with limited evidence for optimal second‐line therapy. This study describes the management and outcomes of relapsed RMS patients in France. Methods We retrospectively reviewed all nonmetastatic RMS patients enrolled in France in the RMS 2005 study who relapsed between 2006 and 2019 after achieving complete local control, defined as complete remission or stable residue ≥ 6 months after treatment completion. Data were extracted from the RMS 2005 database and medical records. Results Ninety‐five patients relapsed at a median age of 6.0 years (range: 1.0–27.0). The median time from diagnosis to relapse was 17.5 months (range: 7.4–82.0). Most patients had embryonal RMS (65.3%) and local/locoregional relapses (71.6%). The first relapse treatment included chemotherapy (all except two patients), radiotherapy (52.6%), and surgery (48.4%). Second‐line chemotherapy yielded a 58.5% objective response rate after 3 ± 1 cycles. Fifty‐five patients achieved second complete remission. With a median follow‐up of 7.2 years from the first relapse (range: 0.3–11.3), 5‐year progression‐free survival was 26% (95% CI: 18–36), and 5‐year overall survival was 35% (95% CI: 25–45). Importantly, no patient survived relapse without receiving locoregional treatment (surgery and/or radiotherapy). Conclusion This study confirmed the inconsistencies in therapy and the poor prognosis for relapsed RMS but highlighted the potential for long‐term survival in patients who received surgery and/or radiotherapy, emphasizing the crucial role of achieving local control in improving outcomes at relapse.